The Effect Of Financial Ratios To Financial Distress Using Altman Z-Score Method In Real Estate Companies Listed In Indonesia Stock Exchange Period 2014 - 2018 - Ouw Desiyanti; Wahyoe Soedarmo; Kristian Chandra; Kusnadi Kusnadi (Universitas Trisakti, 2019)
Purpose - The purpose of this paper is to find out the effect of Financial Ratio on Financial Distress using Z-Score Altman method.Design/Methodology/approach - This paper uses data from 21 property and real estate companies listed in BEI period 2014-2018 with 105 data observations. The variables used are ROE (Return On Equity), DER (Debt to Equity Ratio), CR (Current Ratio), WCR (Working Capital Ratio) and Z-Score.Findings - The results show that ROE and WCR have a positive significant effect on Z-Score Altman's financial distress, DER and CR have negative significant effect on Z-Score Altman's financial distress. While simultaneously shows that at least one variable have a significant effect on Z-Score Altman financial distress.The financial condition of companies in the real estate sector has worsened over the years, marked by the increasing number of companies that were in financial distress from 5 companies in 2014 to 9 companies in 2018. Likewise with companies in the financial condition of gray areas from 8 companies in 2014 became 9 companies in 2018. While companies with a healthy financial condition decreased from 8 companies in 2014 to 3 companies in 2018.Research limitation/implications - The sample is small, and consequently, findings may not be generalisable to the population.Originality/value - This paper aims to obtain empirical evidence of how financial ratios affect financial distress and also the exposure of financial distress probabilities to real estate companies that are used as research samples.